2020
DOI: 10.1182/bloodadvances.2020003519
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 levels are dramatically high in the sputum from children with sickle cell disease during acute chest syndrome

Abstract: Key Points Sputum interleukin-6 (IL-6) level is high during acute chest syndrome (ACS) in pediatric sickle cell disease, supporting anti–IL-6 trials. Sputum IL-8, CCL2, and CCL3 levels are also high during ACS, possibly contributing to recruitment of inflammatory cells in the lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…2 We recently reported a major increase in IL-6, unlike other main pro-inflammatory cytokines, in the sputum and bronchoalveolar fluid from SCD children during ACS. 3 These values were more than 150-fold higher than those observed in plasma, suggesting a predominant local inflammation over systemic inflammation. Furthermore, patients with the highest sputum IL-6 values had the most severe forms of ACS, suggesting a positive correlation between IL-6 concentrations and ACS severity.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…2 We recently reported a major increase in IL-6, unlike other main pro-inflammatory cytokines, in the sputum and bronchoalveolar fluid from SCD children during ACS. 3 These values were more than 150-fold higher than those observed in plasma, suggesting a predominant local inflammation over systemic inflammation. Furthermore, patients with the highest sputum IL-6 values had the most severe forms of ACS, suggesting a positive correlation between IL-6 concentrations and ACS severity.…”
mentioning
confidence: 89%
“…2 Selinexor has good oral bioavailability, and is metabolized primarily by multiple hepatic routes without significant renal metabolism. 3 In addition, it does not directly affect creatinine clearance (CrCl), though it can be associated with asymptomatic hyponatremia, which may be due to increased sodium loss from the kidney. 2 Selinexor is approved by the United States Food and Drug Administration for patients with MM after at least one prior therapy based on the BOSTON study, 4 with no contraindications based on renal dysfunction.…”
mentioning
confidence: 99%
“…Accumulating evidence has long identified chronic low-grade inflammation as a risk factor for the progression of myocardial infarction, ventricular hypertrophy, cardiac fibrosis, diastolic dysfunction, and pulmonary hypertension in the general population [6][7][8][9][10] . Recent mechanistic and observational studies on cardiopulmonary complications of SCD implicate inflammation as a major player in the onset and progression of cardiopulmonary complications in SCD [11][12][13][14][15][16] . These include several studies in animals and humans on the development of acute chest syndrome (ACS), cardiac hypertrophy, pulmonary hypertension (PH), cardiac fibrosis, and diastolic dysfunction [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent mechanistic and observational studies on cardiopulmonary complications of SCD implicate inflammation as a major player in the onset and progression of cardiopulmonary complications in SCD [11][12][13][14][15][16] . These include several studies in animals and humans on the development of acute chest syndrome (ACS), cardiac hypertrophy, pulmonary hypertension (PH), cardiac fibrosis, and diastolic dysfunction [11][12][13][14][15] . These studies consistently suggested inflammatory pathways as a vital unifying mechanism that accompanies the structural and functional changes that occur at the onset and Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…Increased IL-6 levels in sputum might reflect the recruitment of innate immune cells, including monocytes, in the lungs. Indeed, the main chemokine found in sputum during ACS is monocyte-chemoattractantprotein-1 (MCP1), 3 and monocyte stimulation by free HbS was recently shown to induce a predominant increase in IL-6 production mediated by TLR4. 6 In our study, hemoglobin level was negatively correlated with sputum IL-6 level, which supports the hypothesis of a role for hemolysis, leading to the release of free HbS and heme, in ACS pathophysiology.…”
mentioning
confidence: 99%